Left ventricular mechanical dispersion in flow-gradient patterns of severe aortic stenosis. (25th November 2020) - Lavall, D; Kuprat, L.K; Kandels, J; Stoebe, S; Hagendorff, A; Laufs, U
Abstract: Purpose: Patients with severe aortic stenosis are classified according to flow-gradient patterns. We investigated whether left ventricular (LV) mechanical dispersion, a marker of dyssynchrony and predictor of mortality, is associated with low-flow status in aortic stenosis. Methods and results: 400 consecutive patients with QRS duration <120ms were included in the retrospective analysis. Patients with severe aortic stenosis (aortic valve area ≤1.0cm 2 ) were classified as normal-flow (NF; stroke volume index >35ml/m 2 ) high-gradient (HG; mean transvalvular gradient ≥40mmHg) (n=79), NF low-gradient (LG) (n=62), low-flow (LF) LG ejection fraction (EF) ≥50% (n=57), and LF LG EF<50% (n=23). Patients with moderate aortic stenosis (aortic valve area 1.5–1.0cm 2 ; n=95) and patients with chronic systolic heart failure (n=84) without aortic stenosis served as comparison groups. Similar values of mechanical dispersion (calculated as standard deviation of time from Q/S onset on electrocardiogram to peak longitudinal strain in 17 left ventricular segments) was observed in patients with NF HG (49.4±14.7ms), NF LG (43.5±12.9ms), LF LG EF≥50% (47.2±16.3ms) and moderate aortic stenosis (44.2±15.7ms). Mechanical dispersion was increased in patients with LF LG EF<50% (60.8±20.7ms) and in chronic heart failure (59.4±16.7ms) (p<0.05 for both vs. NF HG ‡, NF LG †, LF LG EF≥50% § and moderate*; Figure). Mechanical dispersion correlated with LV end-systolic volume index (r=0.2530, p<0.0001), LVEF (r=−0.2895, p<0.0001) and global longitudinal strain (r=0.3108, p<0.0001), but not with parameters of aortic stenosis. Conclusion: Mechanical dispersion was similar among flow-gradient subgroups of severe aortic stenosis with preserved LVEF, but increased in patients with low-flow low-gradient and reduced LVEF. These findings indicate that mechanical dispersion is rather a marker of systolic myocardial dysfunction than of aortic stenosis. Funding Acknowledgement: Type of funding source: None